2013
DOI: 10.4318/tjg.2013.0709
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization for treatment of hepatocellular carcinoma: A single center experience

Abstract: Amaç: Hepatosellüler karsinomlu hastalarda transarteriyel kemoembolizasyon tedavisinin sa¤kal›m üzerine olan etkisi ve iki farkl› transarteriyel kemoembolizasyon yöntemi olan konvansiyonel transarteriyel kemoembolizasyon ve ilaç sal›n›ml› partiküllü transarteriyel kemoembolizasyon tedavilerinin etkinlik ve tahammül edilebilirli¤inin araflt›r›lmas›d›r. Gereç ve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…There are some studies that calculate the Child-Pugh score, which calculates hepatic function and estimates severity of cirrhosis [ 12 ]. These studies used the score as inclusion criteria for TACE, using only patients in Child-Pugh class A or B [ 13 , 14 ]. Patients in class A may have better long-term outcomes than those in class B [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies that calculate the Child-Pugh score, which calculates hepatic function and estimates severity of cirrhosis [ 12 ]. These studies used the score as inclusion criteria for TACE, using only patients in Child-Pugh class A or B [ 13 , 14 ]. Patients in class A may have better long-term outcomes than those in class B [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies used the score as inclusion criteria for TACE, using only patients in Child-Pugh class A or B [ 13 , 14 ]. Patients in class A may have better long-term outcomes than those in class B [ 13 , 15 ]. Our patient’s Child-Pugh score was 7, putting him in class B.…”
Section: Discussionmentioning
confidence: 99%
“…While TACE may be a safe oncological intervention in select patients with Child–Pugh class B/C cirrhosis, previous studies have demonstrated that Child–Pugh classification is significantly associated with post‐TACE complications, and the development of radiocontrast‐induced nephropathy post‐TACE . Many studies have also confirmed that Child–Pugh class is significantly associated with survival post‐TACE . Other studies have reported on the individual components of the Child–Pugh scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…A common modification of this procedure is the co‐delivery of an embolizing agent to restrict arterial bloodflow and induce ischemia in addition to the chemotherapeutic effect of DOX, a technique called transarterial chemoembolization (TACE) . Unfortunately, HAI and TACE are severely hindered by high complication rates such as dose‐limiting toxicities (e.g., cardiotoxicity, myelosuppression, and hepatic failure), high rates of tumor recurrence, and development of chemoresistance . Off‐target toxicity arises mainly from the leakage of DOX into the systemic circulation leading to the unintended delivery of DOX to surrounding healthy tissue, while chemoresistance develops through upregulation of drug efflux pumps in response to xenobiotic compounds such as DOX …”
Section: Introductionmentioning
confidence: 99%